Private school teachers' voice in the Philippines amidst Covid-19 pandemic: A descriptive phenomenological study - Bernardo K. Gumarang Jr (Northern Negros State College of Science and Technology (NONESCOST), 2021)
Several studies discovered that private teachers have a higher probability of losing their jobs than public school teachers during the Global Financial Crisis. This appears to be the case in many low- and middle-income countries throughout the current crisis or covid-19 pandemic. This phenomenon is generating a lot of problems, particularly as voiced out by private school teachers in the context of developing countries. This motivates the researcher to investigate and discuss the problems faced by private school teachers in the Philippines in the wake of the Covid-19 crisis. Specifically, the researcher described their motivation factors teaching in the private school and their challenges during a Covid-19 pandemic. The researcher used a descriptive phenomenological research approach and an in-depth interview. Using purposive sampling, seven (7) participants were selected to participate in the study. To preserve the confidentiality of the research participants, ethical measures were also implemented. The responses of the participants were thematically analyzed using Colaizzi's methods of descriptive phenomenology. Results revealed 3 themes on the motivation factors: Passion in Teaching, Teaching as a Calling and Promotion in Public School and 5 themes related to challenges which include Financial Constraints, Mental Health Issues, Working beyond Contract, Lack of Teaching Resources and Poor Relationship with the School Heads. Indeed, private teachers are also encountering problems that need to be addressed by the national government. As voiced out by the participants they received nothing from the government as compared to the public teachers during the pandemic. This study recommends that the national government must also look at how to help private teachers who are affected by the pandemic, such as financial assistance. Private school institutions may also consider creating policies to address some issues encountered by their employees.